EFFECTIVENESS OF COUNSELING SESSIONS TO PROVIDE ERROR ANALYSIS TO IMPROVE THE ENGLISH FUNCTIONAL SKILLS OF THE UNDERGRADUATE STUDENTS OF UCP, LAHORE - Rakhshanda Furnaz; Hamza Amin; Dr. Farhat Meher (International Journal of Contemporary Issues in Social Sciences, 2024)
This paper summarizes a quasi-experimental study of the effectiveness of counseling sessions to improve language learning of foreign or second language learners. Students of the University of Central Punjab were provided with after-university, counseling sessions during the COVID-19 online semester Fall 21. It was assumed that due to online classes, regular class interaction with the teacher aimed to deliver lectures is not enough to build rapport with students and brush up their functional skills. So, the idea was to especially arranged counseling sessions in the evening after study time so that students may have time to reflect on the lecture and develop some questions related to English grammar and skills. The consolidated data has been attached in which it is observed that students have different social and psychological pressure and these sessions motivated them to participate in the classroom discussion benefited from these counseling sessions to get individual attention from teachers to improve their teaching and learning process.